A Study About Library Usage by Undergraduate Medical Students in A Medical College in North India - Goel, N K; Sarpal, S S; Galhotra, Abhiruchi; Abhadeep (National Journal of Community Medicine, 2012)
Background: Since no study has been done regarding use of library in medical students in North India and very few studies in whole of India that is why this study was conceived. Objective: To study the use of library by medical students in all the professional courses in Government Medical College, Chandigarh U.T. Material and Methods: 235 students were administered pre-structured and pre-tested proforma in classroom and guided filling of proforma was done by authors. Results: Maximum students (265) were in the age group of 18-25 years.122 students felt that their objectives were partially fulfilled in the library, 71 felt their objectives were fully fulfilled in the library, while 20 felt none of their objectives were fulfilled in the library. 64.5 % students were visiting library for updating their knowledge, 31.7% for retrieving literature, 18.7% for information on a specific disease, 12.6% for research purposes, 6.7% for diagnosis, 2.6% for publications, 2.2% for patient care. Among the IT services available 57% were using computer, 54.1% were utilising internet, 47.01% were using E mail, 32.5% were using E books, 31.3%were using CD ROM, and 28.3% were using telephone. Out of benefits available of using IT services 75.7% said it lead to better access to information, 51.8% said it provided quick information, 42.9% said it lead to contact with distant personnel, 44.75% believed it lead to improvement in quality of work, 22.7%said it lead to decrease in use of postal mail, 10.8% said it lead to decrease in use of telephone, 10.1% said it lead to decrease in use of print version. 34.3 %( 91) students opined that there was need for an orientation programme regarding the use of IT services in the library.